Strategi Manajemen Keuangan untuk Usaha Mikro: Pendekatan Pengabdian Masyarakat dalam Meningkatkan Kemandirian Ekonomi - Sutarjo, Sutarjo; Rosari, Dini; Purnomo, Yudiyanto Joko; Elshifa, Aria; Aisyah, Siti (Civiliza Publishing, 2025)
The national economy depends on micro, small and medium enterprises (MSMEs). Unfortunately, many people face problems with financial management. This can hinder the progress and sustainability of the business. The purpose of this study is to reveal successful financial management methods. To improve the economic independence of micro-entrepreneurs, we use the community service method. We use a comprehensive and in-depth qualitative approach. We explore the meaning thoroughly through in-depth interviews, participant observation, and document review. Studies show that collaboration can produce extraordinary results. To achieve this goal, do three things. First, manage finances simply and in a targeted manner. Second, provide financial training. Third, provide intensive assistance. This process significantly increases the effectiveness and efficiency of micro-businesses. This is a practical suggestion for community service institutions. With real support, the growth of small and medium enterprises (MSMEs) can move in a brighter direction.